Adoption of the composting practice in the farmer field school of San Mateo Piñas, Oaxaca, Mexico - Mariano, Morales-Guerra; Pedro, Cadena-Iñiguez; Yuliana, Cadena-Pérez Karla; Venancio, Cuevas – Reyes; Cuauhtémoc, Ramírez-García Uriel (Edelweiss Applied Science and Technology, 2024)
The adoption of agricultural technology is a process that involves the participation of various stakeholders. Evaluating this process is important for identifying factors that either limit or promote the use of new technologies in rural areas. The objective of this research was to estimate the degree of adoption of compost technology, as well as the variables that influence the use of this agroecological practice among small rural producers from a field school in the municipality of San Mateo Piñas, Oaxaca, Mexico. Using probabilistic sampling, 36 producers from a field school focused on coffee production were selected. A questionnaire was applied, covering topics related to socioeconomic and productive aspects, along with a technical sheet to evaluate the variables related to the adoption of compost. A total of 96% of producers reported being familiar with the technology, 88% had prepared and tested it in the field, and 54% had adopted it in the coffee production process. Additionally, a positive and moderate correlation was found, with a value of r(21)=.456, p=.029, between adoption and the variable related to the individual preparation of compost. The technical support provided through the field school approach facilitated the individual adoption of compost technology and identified areas of opportunity that could allow for greater degrees of adoption of new technologies.